Ophthalmological profile of patients with thyroid diseases in Fortaleza, Ceará, Brazil: glaucoma investigation - Castro, Bianca Diogo Lessa; Sobral, Sandy Ester Freire; Pereira, Pedro Henrique de Santana; Cordeiro, Aline Lourenço; Santos, Sarah Dibe; Costa, Ana Adélia Sá; Ribeiro, Herculano Pontes Barros; Gradvohl, Hissa Tavares de Lima; Lopes, Laura da Silva Girão; Ferreira, Juliana de Lucena Martins (Journal of Health & Biological Sciences, 2021)
Objective: To evaluate the prevalence of ophthalmological pathologies, between thyroidopathies, for early diagnosis of glaucoma in patients seen at the Clínica Escola de Saúde (CES) of the Medicine Center of the Centro Universitário Christus (UNICHRISTUS), Fortaleza – Ceará – Brazil. Methods: A cross-sectional study and descriptive analysis of medical records of patients diagnosed with hypothyroidism or hyperthyroidism by the International Classification of Diseases (ICD-10) on the CES electronic system, between 2013 and 2018. Screened patients were invited to perform an eye examination at Fundação Leiria de Andrade (FLA). Results: Of the 499 medical records screened, 22.8% (114) had a confirmed diagnosis for thyroid disorders, 85.9% (98) with hypothyroidism, and 14.0% (16) with hyperthyroidism. Of these, 72.0% (101) were women and 28.0% (13) men. The most prevalent age group was between 41 and 60 years old, corresponding to 46.4% (53), being 65.7% (75) from Fortaleza - Ceará. The main comorbidities associated with thyroid diseases were systemic arterial hypertension, 43.8% (50), followed by dyslipidemia, 26.3% (30), and type 2 diabetes mellitus in 13.1% of patients (15). Of the total, 25 patients were referred to the FLA, 84.0% (21) reported previous eye diseases, 4.0% (1) diagnosticated with increased constitutional excavation, and 12.0% (3) with a diagnosis of primary open-angle glaucoma. Conclusion: Despite the hypothesis of an association between glaucoma and thyroidopathy, the sample size didn’t allow inferences about the increased risk of its correlation, as well as in other pre-existing studies in the literature, requiring further studies to elucidate this relevant association.